Efektivitas Model Problem Based Learning Berbasis Outdoor Study terhadap Hasil Belajar Geografi Kelas X SMA Negeri 1 Majene - Kusuma, Ananda Tryo; Maddatuang, Maddatuang; Hasriyanti, Hasriyanti; Amdah, Misdar; Abidin, Muhammad Rais (UNIVERSITAS NEGERI MAKASSAR, 2025)
Geography learning requires a strong connection between theoretical concepts and real environmental conditions; therefore, an instructional model that provides direct learning experiences is needed. This study aims to determine the effectiveness of the Problem Based Learning (PBL) model integrated with Outdoor Study on the geography learning outcomes of tenth-grade students at SMA Negeri 1 Majene. A quantitative approach was employed using a Pretest–Posttest Control Group design, with the sample selected through purposive sampling. The research instruments included achievement tests, student response and activity questionnaires, and an N-gain analysis to measure learning improvement. The results indicate that the PBL model with Outdoor Study is more effective than conventional teaching, with an average score of 82.75 in the experimental class compared to 66.88 in the control class. The N-gain score of the experimental class reached 0.66 (high category), while the control class obtained only 0.14 (low category). Furthermore, students’ responses toward the learning model showed a positive category. Therefore, it can be concluded that the PBL model based on Outdoor Study is effective in improving geography learning outcomes.AbstrakPembelajaran geografi menuntut adanya keterkaitan antara konsep teoritis dengan realitas lingkungan, sehingga diperlukan model pembelajaran yang mampu menghadirkan pengalaman belajar secara langsung. Penelitian ini bertujuan untuk mengetahui efektivitas model Problem Based Learning (PBL) berbasis Outdoor Study terhadap hasil belajar geografi siswa kelas X SMA Negeri 1 Majene. Penelitian menggunakan pendekatan kuantitatif dengan desain Pretest-Posttest Control Group, dan sampel ditentukan melalui teknik purposive. Instrumen yang digunakan meliputi tes hasil belajar, angket respon dan aktivitas siswa, serta analisis peningkatan nilai melalui perhitungan N-gain. Hasil penelitian menunjukkan bahwa penerapan model PBL berbasis Outdoor Study lebih efektif dibandingkan pembelajaran konvensional, dengan rata-rata hasil belajar 82,75 pada kelas eksperimen dan 66,88 pada kelas kontrol. Nilai N-gain pada kelas eksperimen sebesar 0,66 (kategori tinggi), sedangkan kelas kontrol hanya 0,14 (kategori rendah). Selain itu, respon siswa terhadap pembelajaran menunjukkan kategori positif. Dengan demikian, dapat disimpulkan bahwa model PBL berbasis Outdoor Study efektif dalam meningkatkan hasil belajar geografi.